BATAS KEWAJIBAN ANAK BEKERJA DALAM KAJIAN HUKUM KELUARGA ISLAM - Hidayat, Iman Nur; Hermanto, Agus; Nurnazli, Nurnazli (Ijtimaiyya: Jurnal Pengembangan Masyarakat Islam, 2021)
Children are the responsibility of parents, as long as they are not mature (adult) as their needs are the responsibility of parents, but when they grow up there are limits in both normative and positive laws that allow children to work, in reality many children are already working looking for income under the specified age. The problem is when can children work in both normative and positive law? This research is to be able to clearly describe a rule that applies, so that parents do not employ underage children. This research is a library research, namely a literature review of the views of the scholars and the laws and regulations in Indonesia with a philosophical-sociological approach. From a normative legal perspective, scholars agree that a child who has reached puberty can only carry out his religious obligations, including work, because he is considered an adult, while in Indonesian legislation, a child is said to be an adult when he is 21 years old, so that at that age, the child has an established mind, physically and psychologically.